Optimization of temperature and extraction time for the nutritional and phytochemical contents of corn bran with ultrasonic-method - Haslina Haslina; Dewi Larasati; Ery Pratiwi; Novizar Nazir; Ika Fitriana (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2021)
One of the natural antioxidants sources that have the potential to be utilized as raw material for functional food is corn bran. Corn bran is a by-product of the milling process of corn that is gaining attention as a functional food is increasing in recent years. This study aimed to optimize temperature and extraction time for the nutritional and phytochemical contents of corn bran with ultrasonic-method. Optimized Custom Design was applied to investigate the effect of experimental factors on the nutritional and phytochemical contents. This study used Randomized Block Design (RBD) arranged in-factorial with 3 treatments, namely temperature and time of extraction. Temperature: A1=500C, A2=550C, A3=600C, and A4=650C, and time: B1=10 minutes, B2=15 minutes, B3=20 minutes, and B4=25 minutes. The data obtained were analyzed statistically using ANOVA with a significance level of 95% and then processed with Software DX13.0 ® program. The results of the research show the formula of the experiment which is optimal at a temperature of 500C and 10 minutes. In this condition, the result is the yield at 38.34%, nutritional contents (water at 9.17%; ash at 0.33%; fat at 1.33%, protein at 4.40%, carbohydrates at 85.47%; and crude fiber at 1.88%. produce yield 38.34%, and phytochemical contents (total phenols at 1778.07 µg GAE/g. flavonoids at 92.11 µg GAE/g, vitamin C at 5.84 mg, antioxidant activity at 43.33%, and tannins at 0.11%). This study implies that there is an increase in added value from the conversion of corn bran into nutrient-rich products and has a promising phytochemical content.